Considering the articulation and grammar of mother tongue of foreign learner in russian language training (Eurasian Journal of Philology Science and Education, 2016)
The article places emphasis on the importance of taking into account aspects peculiar to the articulation of foreign students, especially of both Dari and Pashto as native or official languages. Particular attention is paid to the roots of phonetic errors made by foreign students. We systematically practice the students’ correct pronunciation and identify the impact of the phonetic particularities of the students’ native languages simultaneously. Moreover, we practice correct pronunciation of both Russian individual sounds and compound sounds. Practical Russian phonetics employs the differentiation of universal, typological and specific aspects of Russian phonographic system. Studies of foreign accents of non-native speakers of Russian have demonstrated the absence of similar features of the analysed accents. Nonetheless, the phonographic system of the Russian language has some segments, which indicate phonetic interference effects. Articulators are similar for the speakers of all languages. Nevertheless, each language has a specific system of producing speech sounds.
Keywords: articulation of foreign listeners; specific of pronunciation; give the mother tongues Pashto; universal lines of accent; phonetic system of Russian; phonetic interference.